Transformasi Perawatan Kesehatan Ibu Hamil dengan IoT: Solusi Cerdas untuk Pemantauan Real-Time di Daerah Terpencil - Oktarina, Eka Sari; Alamsyah, Gempar; Nurhalissa, Rahmalia; Satria, Rahul Fahmi (Jurnal Algoritma, 2025)
The high maternal and infant mortality rates in developing countries remain a major challenge in public health. Contributing factors include poverty, limited healthcare infrastructure, and cultural norms that restrict access to medical services. One of the main obstacles is the lack of continuous and real-time monitoring of pregnant women's health, which leads to delays in detecting pregnancy complications. Although various efforts have been made, there is still a gap in the use of technology capable of practically and accurately monitoring maternal health conditions in the field. This study aims to develop an Internet of Things (IoT) device to measure maternal health parameters such as height, weight, blood pressure, and fetal heart rate, with real-time data transmission to the cloud using Firebase. Testing was conducted on 15 pregnant women in Malang Regency, comparing the IoT device's measurements with standard measuring instruments. The results showed high accuracy, with an average error of 0.45% for height and 0.29% for weight. Systolic blood pressure measurements showed greater error variation (7.71%–21.45%), while diastolic pressure was more stable (1.81%–8.95%). Data transmission to Firebase showed an average delay between 1.75 and 2.69 seconds without data loss, indicating that the communication system operated optimally and maintained information integrity. This IoT device has the potential to support real-time monitoring of maternal health, thereby facilitating early medical intervention and contributing to reducing maternal and infant mortality in developing regions.